An Overview of the Use of Artificial Intelligence Tools in Agriculture - Surwase, Samadhan; Kadu, Prakash; More, Sagar (Current Research Progress in Agricultural Sciences Vol. 4, 2024)
The next generation is dedicated to farming and looks forward to achieving high productivity through the use of new technologies. Technology should create a framework that will help farmers in every aspect of farming from land preparation to seed selection and fertilization. Farmers can also rely on market analysis and consumer demand to help them achieve better results. Artificial Intelligence (AI) based farming increases farmer’s profits by producing higher yields and better profits. AI has emerged as a powerful tool that can revolutionize the agricultural sector by enhancing crop productivity, optimizing resource utilization and improving the decision-making processes. AI is being used in applications such as weather forecasting and automatic machine adjustment for disease or pest identification. By using sensors and other devices incorporated in robots and drones, artificial intelligence can be used in agriculture for irrigation, weeding, and nutrient spraying and help sustain soil fertility and efficient farming. Technology-based agriculture will soon attract the next generation to work in agriculture. This method will help farmers understand market needs by making predictions. This report explores the various applications of AI in agriculture and their potential benefits.